2019
DOI: 10.1101/819409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Assessment of the Regulation-Modulating Potential for Noncoding Variants

Abstract: 26Large-scale genome-wide association and expression quantitative trait loci studies have identified 27 multiple noncoding variants associated with genetic diseases via affecting gene expression. 28However, effectively and efficiently pinpointing causal variants remains a serious challenge. Here, 29we developed CARMEN, a novel algorithm to identify functional noncoding expression-30 modulating variants. Multiple evaluations demonstrated CARMEN's superior performance over 31 state-of-the-art tools. Its higher s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…We used 2403 trained CNNs to annotate the functional effects of expression-modulating variants [26]. Most of the trained CNN networks were accurate, with an average AUROC of 0.908 and an average AUPRC of 0.904.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used 2403 trained CNNs to annotate the functional effects of expression-modulating variants [26]. Most of the trained CNN networks were accurate, with an average AUROC of 0.908 and an average AUPRC of 0.904.…”
Section: Resultsmentioning
confidence: 99%
“…By the end of November 2019, REVA consisted of 11,862,367 entries covering 5,948,789 experimentally tested noncoding loci across 18 cell cultures from 14 publications [4,8,11,[29][30][31][32][33][34][35][36][37][38][39]. We first excluded loci tested in mice (15,152) and with more than one alternative allele (26,326 (Figure 2A, Supplementary Table S2). We found that both positive and negative variants were unevenly distributed on chromosomes, and no variants were located on the Y chromosome ( Figure 2B, Supplementary Table S3).…”
Section: Characterization and Distribution Of Expression-modulating Vmentioning
confidence: 99%
See 1 more Smart Citation